2004
DOI: 10.1023/b:myco.0000020593.75809.91
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Candida and mode of action of two newly synthesized polymers: a modified poly (methylmethacrylate-co-vinylbenzoylchloride) and a modified linear poly (chloroethylvinylether-co-vinylbenzoylchloride) with special reference to Candida albicans and Candida tropicalis

Abstract: Polymeric antimicrobial agents represent a new and important direction that is developing in the field of antimicrobial agents. Antimicrobial activity of two newly synthesized polymers: a modified poly (methylmethacrylate-co-vinylbenzoylchloride) and a modified linear poly (chloroethylvinylether-co-vinylbenzoylchloride) have been investigated and found to be active. Both polymers have showed a broad antimicrobial activity against C. albicans and C. tropicalis. Minimal inhibitory concentrations (MIC's) for poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…They found that thienopyrimidine derivatives inhibits dihydrofolate reductase (DHFR) which plays an essential role in carbon metabolism, which is critical to the biosynthesis of DNA, RNA, and the essential amino acid methionine. However, the effect of the compound no.20 on protein banding pattern in C. albicans coincide with that obtained with Mahmoud and Aly (20). They found that the effect of synthesized polymers modified poly (methylmethacrylate-co-vinylbenzoylchloride) and a modified linear poly (chloroethylvinylether-co-vinylbenzoylchloride) on C. albicans indicated no clear effects in the phosphopeptidomannan molecular weight with main bands at 45, 25 and 15 kDa.…”
Section: Respiratory Activitysupporting
confidence: 82%
See 4 more Smart Citations
“…They found that thienopyrimidine derivatives inhibits dihydrofolate reductase (DHFR) which plays an essential role in carbon metabolism, which is critical to the biosynthesis of DNA, RNA, and the essential amino acid methionine. However, the effect of the compound no.20 on protein banding pattern in C. albicans coincide with that obtained with Mahmoud and Aly (20). They found that the effect of synthesized polymers modified poly (methylmethacrylate-co-vinylbenzoylchloride) and a modified linear poly (chloroethylvinylether-co-vinylbenzoylchloride) on C. albicans indicated no clear effects in the phosphopeptidomannan molecular weight with main bands at 45, 25 and 15 kDa.…”
Section: Respiratory Activitysupporting
confidence: 82%
“…Poly (chlorethyvinylether-co-vinylbenzoylchloride) increased respiration for C. albicans and C. tropicials (20) as that observed with the effect of the compound no.20 on C. albicans respiration. This effect may be indicates that many chemical compounds interfering directly with electron transfer or uncoupled oxidative phosphorylation from electron transport.…”
Section: Respiratory Activitysupporting
confidence: 62%
See 3 more Smart Citations